Expression Profiling and Comparative Genomics Identify a Conserved Regulatory Region Controlling Midline Expression in the Zebrafish Embryo - Dickmeis, Thomas; Plessy, Charles; Rastegar, Sepand; Aanstad, Pia; Herwig, Ralf; Chalmel, Frédéric; Fischer, Nadine; Strähle, Uwe

(untitled) (Genome Research, 2004)
Differential gene transcription is a fundamental regulatory mechanism of biological systems during development, body homeostasis, and disease. Comparative genomics is believed to be a rapid means for the identification of regulatory sequences in genomes. We tested this approach to identify regulatory sequences that control expression in the midline of the zebrafish embryo. We first isolated a set of genes that are coexpressed in the midline of the zebrafish embryo during somitogenesis stages by gene array analysis and subsequent rescreens by in situ hybridization. We subjected 45 of these genes to Compare and DotPlot analysis to detect conserved sequences in noncoding regions of orthologous loci in the zebrafish and Takifugu genomes. The regions of homology that were scored in nonconserved regions were inserted into expression vectors and tested for their regulatory activity by transient transgenesis in the zebrafish embryo. We identified one conserved region from the connective tissue growth factor gene (ctgf), which was able to drive expression in the midline of the embryo. This region shares sequence similarity with other floor plate/notochord-specific regulatory regions. Our results demonstrate that an unbiased comparative approach is a relevant method for the identification of tissue-specific cis-regulatory sequences in the zebrafish embryo.